Variability in the subtropical-tropical cells and its effect on near-surface temperature of the equatorial Pacific: a model study - J. F. Lübbecke; C. W. Böning; A. Biastoch (Ocean Science, 2008)
A set of experiments utilizing different implementations of the global ORCA-LIM model with horizontal resolutions of 2°, 0.5° and 0.25° is used to investigate tropical and extra-tropical influences on equatorial Pacific SST variability at interannual to decadal time scales. The model experiments use a bulk forcing methodology building on the global forcing data set for 1958 to 2000 developed by Large and Yeager (2004) that is based on a blend of atmospheric reanalysis data and satellite products. Whereas representation of the mean structure and transports of the (sub-) tropical Pacific current fields is much improved with the enhanced horizontal resolution, there is only little difference in the simulation of the interannual variability in the equatorial regime between the 0.5° and 0.25° model versions, with both solutions capturing the observed SST variability in the Niño3-region. The question of remotely forced oceanic contributions to the equatorial variability, in particular, the role of low-frequency changes in the transports of the Subtropical Cells (STCs), is addressed by a sequence of perturbation experiments using different combinations of fluxes. The solutions show the near-surface temperature variability to be governed by wind-driven changes in the Equatorial Undercurrent. The relative contributions of equatorial and off-equatorial atmospheric forcing differ between interannual and longer, (multi-) decadal timescales: for the latter there is a significant impact of changes in the equatorward transport of subtropical thermocline water associated with the lower branches of the STCs, related to variations in the off-equatorial trade winds. A conspicuous feature of the STC variability is that the equatorward transports in the interior and along the western boundary partially compensate each other at both decadal and interannual time scales, with the strongest transport extrema occurring during El Niño episodes. The behaviour is rationalized in terms of a wobbling in the poleward extents of the tropical gyres, which is manifested also in a meridional shifting of the bifurcation latitudes of the North and South Equatorial Current systems.